2005
DOI: 10.1007/s00221-005-0210-z
|View full text |Cite
|
Sign up to set email alerts
|

Coordination between posture and movement: interaction between postural and accuracy constraints

Abstract: We examined the interaction between the control of posture and an aiming movement. Balance control was varied by having subjects aim at a target from a seated or a standing position. The aiming difficulty was varied using a Fitts'-like paradigm (movement amplitude=30 cm; target widths=0.5, 1.0, 2.5 and 5 cm). For both postural conditions, all targets were within the reaching space in front of the subjects and kept at a fixed relative position with respect to the subjects' body. Hence, for a given target size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 40 publications
3
32
0
7
Order By: Relevance
“…When normal BMI subjects aim at targets of various difficulties, MTs are faster when they perform the task from a seated than from a standing posture. 20 In a different study, Savelsbergh et al 21 observed that children were able to catch more balls in a seated compared to a standing condition. 21,22 These experiments clearly suggest that a stable or controlled platform allows to improve the speed-accuracy characteristics of upperlimb movements.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…When normal BMI subjects aim at targets of various difficulties, MTs are faster when they perform the task from a seated than from a standing posture. 20 In a different study, Savelsbergh et al 21 observed that children were able to catch more balls in a seated compared to a standing condition. 21,22 These experiments clearly suggest that a stable or controlled platform allows to improve the speed-accuracy characteristics of upperlimb movements.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 These experiments clearly suggest that a stable or controlled platform allows to improve the speed-accuracy characteristics of upperlimb movements. [20][21][22] An alternative explanation for the increased MT relates to the mechanical consequence of the greater inertial load of the arm and forearm of the obese subjects. According to this hypothesis, moving heavier segments would require more force, and this could lead to a longer MT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When aiming for a target as fast as possible, the speed and accuracy of a movement are two constraints that are used to define the motor performance. The relationship between these two variables has been formalized as Fitts' law [1,15,16]. It states that movement time (MT) is a linear function of the index of difficulty (ID = Log2 [2A/W]), where A is the amplitude of the movement and W the width of the target (accuracy constraint).…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…1) was assessed using a Fitts-like paradigm [1,15,16]. When aiming for a target as fast as possible, the speed and accuracy of a movement are two constraints that are used to define the motor performance.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%